2018
DOI: 10.1055/s-0038-1675605
|View full text |Cite
|
Sign up to set email alerts
|

METoclopramide Administration as a Strategy to Overcome MORPHine-ticagrelOr Interaction in PatientS with Unstable Angina PectorIS—The METAMORPHOSIS Trial

Abstract: Extensive search for methods of overcoming morphine-related delay of the absorption and onset of action of oral P2Y12 inhibitors in patients presenting with acute coronary syndrome is on-going. The aim of the trial was to investigate whether metoclopramide co-administration could reduce this delay and improve the pharmacokinetics (PKs) and pharmacodynamics (PDs) of ticagrelor and its active metabolite AR-C124900XX. Plasma concentration of both compounds and platelet reactivity were evaluated in nine pre-define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…19 On the other hand, metoclopramide which increases gastrointestinal motility was effective in improving the antiplatelet effects of ticagrelor in the presence of morphine. 20 Alternatively, bridging with cangrelor, an intravenous P2Y12 inhibitor may be an effective strategy for tackling delayed bioavailability of oral P2Y12 inhibitors. 21 After adjustment for multiple comorbidities and hospital effect, each 1 mg of morphine equivalent was associated with a 1.4% increase in peak CK; however, this was no longer statistically significant after adjusting for TIMI flow pre-PCI.…”
Section: Resultsmentioning
confidence: 99%
“…19 On the other hand, metoclopramide which increases gastrointestinal motility was effective in improving the antiplatelet effects of ticagrelor in the presence of morphine. 20 Alternatively, bridging with cangrelor, an intravenous P2Y12 inhibitor may be an effective strategy for tackling delayed bioavailability of oral P2Y12 inhibitors. 21 After adjustment for multiple comorbidities and hospital effect, each 1 mg of morphine equivalent was associated with a 1.4% increase in peak CK; however, this was no longer statistically significant after adjusting for TIMI flow pre-PCI.…”
Section: Resultsmentioning
confidence: 99%
“…The PERSEUS (Platelet Inhibition After Pre‐hospital Ticagrelor Using Fentanyl Compared to Morphine in Patients With ST‐segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention) randomized trial (NCT02531165) will investigate the pharmacokinetics and pharmacodynamics of prehospital ticagrelor in patients with STEMI receiving either fentanyl or morphine. Coadministration of the antiemetic metoclopramide with morphine was recently shown to enhance ticagrelor absorption and platelet inhibition compared with morphine treatment alone in patients with unstable angina …”
Section: Discussionmentioning
confidence: 99%
“…So for patients with ACS without morphine usage at high ischemic risk, it is still a question how to increase the concentration of bioactive metabolites to accelerate the antiplatelet effect of ticagrelor. Recently Sikora observed that co-administration of metoclopramide overcame the delayed onset of P2Y 12 inhibitors caused by morphine among patients with unstable angina, but not for patients with STEMI [15]. The result was mainly caused by drug pharmacology of metoclopramide, which enhanced gastrointestinal tract motility and contractility.…”
Section: Discussionmentioning
confidence: 99%